Value investing in the stock market of Thailand - Gerardo Gerry Alfonso Perez (International Journal of Financial Studies, 2017)
Value investment and growth investment have attracted a large amount of research in recent decades, but most of this research focuses on the U.S. and Europe. This article covers the Thai stock market which has very different characteristics compared to western markets and even South East Asian countries such as Indonesia or Malaysia. Among South East Asian countries, Thailand has one of the most dynamic capital markets. In order to see if some well-known trends in other markets exist in Thailand the performance of value and growth stocks in the Thai market were analyzed for a period of 17 years using existing style indexes (MSCI) as well as creating portfolios using individual stocks. For this entire period, when using the indexes, returns are statistically significant superior for value stocks compared to growth stocks. However, when analyzing the performance of the market in any given calendar year from 1999 to 2016, the results are much more mixed with in fact growth stocks outperforming in several of those years. Interestingly, when building portfolios using criteria such as low P/E or low P/B the results are not statistically different. Suggesting perhaps that the classification into value or growth stocks is more complex than it would appear. One of the common assumptions of value investing is that those stocks outperform over long periods of time. It might well be that in the Thai case one year is not a long enough period for value stocks to outperform. While there have been some clear efforts over recent years to modernize the stock market of Thailand, it remains relatively underdeveloped, particularly when compared to markets such as the U.S. Hence, its behavior regarding value versus growth investment might be rather different.
Keywords: G11; G15; F62; 330; values investment; growth investment; Thailand